Fighting Strategies to Preserve the Existence of Indonesia’s Multicultural Society Amidst the Currents of Globalization - Eko Budi Sulistio; Ita Prihantika (Journal of Research in Social Science and Humanities, 2025)
Globalization is inevitable, as it has become an integral part of everyday life. As a multicultural society with a rich diversity of cultures and traditions, Indonesia must seek opportunities for some of its cultural elements and traditions to become part of the global culture embraced by the international community. However, in reality, both the Indonesian government and society have mostly focused on restricting or protecting local cultures and traditions from foreign cultural influences. In the long run, this defensive approach may hinder the development and global integration of Indonesia’s multicultural heritage. This study aims to describe offensive strategies to preserve the existence of Indonesia’s multicultural culture in the face of globalization. This research is a literature study, conducted by reviewing and analyzing various scholarly articles and books relevant to the topic. The findings indicate that, so far, both national and local governments have predominantly employed defensive strategies to protect cultural and traditional values from the pressures of globalization. This study recommends the adoption of offensive strategies by both the government and society as a means of ensuring the continued existence of Indonesia’s multicultural culture and its transformation into an integral part of global culture. In doing so, Indonesia’s multicultural traditions can sustain themselves amid the powerful currents of globalization